Utilization of marine diatom Thalassiosira weissflogii as a feed additive in seawater-tolerant Nile tilapia (Oreochromis niloticus, Linnaeus 1758) strain - Huervana, Fredson H.; Dionela, Cleresa S.; de la Torre, Eirene Dorothy S.; del Castillo, Carmelo S.; Traifalgar, Rex Ferdinand M. (Frontiers in Sustainable Food Systems, 2022)
The low omega-3 content of tilapia flesh, when compared to marine fish, affects its marketability. In marine animals, the highly unsaturated fatty acids (HUFAs) can be linked to the oil produced by marine diatoms. Among the marine diatoms, the genus Thalassiosira is known to exhibit high content of HUFAs such as eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA). Thus, in this study, the use of marine diatom Thalassiosira weissflogii as a dietary additive in the seawater-tolerant Nile Tilapia strain was evaluated. One hundred ninety-two, 1.40 ± 0.05g seawater tilapia were randomly allocated into 4 treatment groups in 4 replicates. The first treatment group was fed with a control diet (D0), without the diatoms while treatments 1, 2, and 3 were each fed with diets supplemented with T. weissflogii paste at 2.55% (D1), 6% (D2), and 12% (D3), respectively for 60 days. The diets were isonitrogenous, isolipodic and the omega-3 and omega-6 requirements were satisfied. Results demonstrated that D1 had the highest percent weight gain among treatments. Although not significantly different, other parameters such as percent survival, specific growth rate (SGR), protein efficiency ratio (PER), feed conversion ratio (FCR), and feed intake had desirable results in D1. The proximate composition of seawater tilapia showed that % crude protein was highest in D0 but % crude lipid was highest in D1. The fatty acid composition of tilapia in D1 had the highest omega-3 content at 9.29 mg/g tissue and also had the highest n3:n6 at 2.19. Muscle growth-related genes (MyoD and MYG) were up-regulated while liver genes involved in long-chain polyunsaturated fatty acid synthesis (oni-fads2 and elvol5) were down-regulated in D1 as compared to D0. Feeding the diatom-supplemented diet to tilapia had no significant effects on hepatic cells and intestinal morphology. The results suggested that a 2.55% supplementation dose of T. weissflogii could promote growth and enhance the tissue content of omega-3 fatty acids of the seawater strain Oreochromis niloticus.